Peningkatan Performa Sapi Perah melalui Teknologi Rekayasa Reproduksi di Desa Cijambu, Kecamatan Tanjungsari, Sumedang - Salimah, Aldena Bina; Christi, Raden Febrianto; Tasripin, Didin Supriat; Suryanah, Sari; Suharwanto, Dwi (Farmers: Journal of Community Services, 2025)
This community service program was designed to enhance the knowledge and practical skills of dairy farmers in Cijambu Village, Tanjungsari Subdistrict, Sumedang Regency, regarding the application of reproductive biotechnology. Farmers commonly experienced repeated failures in artificial insemination (AI) due to inaccurate estrus detection and insufficient understanding of reproductive management. The program was conducted through a pre-test, counseling session, discussion, and post-test. Evaluation results showed improved farmer comprehension, as seen in post-test scores: reproductive technology (from 45% to 85%), estrus and reproductive cycles (from 60% to 90%), and reproductive management (from 35% to 80%). This activity effectively enhanced the farmers' capabilities in managing dairy cattle reproduction more optimally.Keywords: dairy cattle, artificial insemination, reproductive technology, counseling